Effects of dried longan seed (Euphoria longana Lam.) extract on VEGF secretion and expression in colon cancer cells and angiogenesis in human umbilical vein endothelial cells - Panyathep A. (2014)
Angiogenesis is a critical event in cancer metastasis, via delivery of needed oxygen and nutrients to tumor cells. Anti-angiogenesis is one strategy for controlling cancer progression. We herein report anti-angiogenesis activity of dried longan seeds using colon adenocarcinoma cells (SW480 cells) and human umbilical vein endothelial cells (HUVECs). Sephadex LH-20 column chromatography was used for separate three dried longan seed fractions. We firstly evaluated vascular endothelial cell growth factor (VEGF) secretion, expression and colony formation of SW480 cells, using enzyme-linked immunosorbent assay (ELISA), Western blot analysis and soft agar assays. Meanwhile cell proliferation, gelatinase activity and tube formation of HUVECs were determined via proliferation assay, gelatin zymography and in vitro tube formation assay, respectively. The results suggest that dried longan seed fractions could be potential angiogenic inhibitors not only interruption of VEGF secretion and expression in SW480 cells but also abrogation of cell proliferation, the activity of gelatinase and tube formation of HUVECs. © 2013 Elsevier Ltd.